Answer:
so b=-9 while c=12.
Step-by-step explanation:
If you have x-intercepts 1 and -4, then that means f(1)=0 and f(-4)=0.
You are given [tex]f(x)=-3x^2+bx+c[/tex]
So you have the system of equations to solve:
[tex]f(1)=-3(1)^2+b(1)+c=0[/tex]
[tex]f(-4)=-3(-4)^2+b(-4)+c=0[/tex]
Evaluating the exponents:
[tex]-3(1)+b+c=0[/tex]
[tex]-3(16)-4b+c=0[/tex]
Doing a little bit of multiplying:
[tex]-3+b+c=0[/tex]
[tex]-48-4b+c=0[/tex]
Let's add 3 on both sides of equation 1 and 48 on both sides of equation 2:
[tex]b+c=3[/tex]
[tex]-4b+c=48[/tex]
Subtracting the equations will eliminate c.
Let's do that:
[tex]5b+0c=-45[/tex]
[tex]5b=-45[/tex]
Divide both sides by 5:
[tex]b=\frac{-45}{5}[/tex]
Simplify:
[tex]b=-9[/tex]
If b=-9 and b+c=3 then -9+c=3 implies c=9+3=12.
so b=-9 while c=12.